2010
DOI: 10.1111/j.1467-629x.2009.00332.x
|View full text |Cite
|
Sign up to set email alerts
|

Divestitures, wealth effects and corporate governance

Abstract: We analyse the market reaction to divestiture decisions and determine the impact of corporate governance practices. We find the market reaction is significant and can be determined using internal governance mechanisms. We evaluate the determinants of the decision to sell using a control sample of firms displaying characteristics often associated with divestitures indicating that these firms may face the same incentives to divest but elect not to restructure in this manner. Our results suggest that a combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…Indeed, more recent empirical evidence generally supports the value-creating nature of divestitures. Netter et al (2011) and Owen, Shi, and Yawson (2010) show that the market does not on average react negatively to divestiture announcements: the short-run returns around divestitures by public US firms are positive and amount to 4.4% and 1.57%. Moreover, Netter et al (2011) further document that when accumulating the abnormal returns from all activities related to the transaction (acquiring a target firm, being a target, and divesting the target), the total shortrun return accrues to over 16%.…”
Section: Post-merger Restructuring and Divestituresmentioning
confidence: 99%
“…Indeed, more recent empirical evidence generally supports the value-creating nature of divestitures. Netter et al (2011) and Owen, Shi, and Yawson (2010) show that the market does not on average react negatively to divestiture announcements: the short-run returns around divestitures by public US firms are positive and amount to 4.4% and 1.57%. Moreover, Netter et al (2011) further document that when accumulating the abnormal returns from all activities related to the transaction (acquiring a target firm, being a target, and divesting the target), the total shortrun return accrues to over 16%.…”
Section: Post-merger Restructuring and Divestituresmentioning
confidence: 99%
“…Ahn & Walker, 2007; Hoskisson & Turk, 1990). Owen, Shi, and Yawson (2010) further demonstrate that given a fundamental need to divest, firms with effective governance are more likely to divest despite the natural reluctance of managers to pursue an activity that reduces the size and private benefits of controlling large firms. Under less effective governance structure, corporate executives may have control of the company without adequate supervisory restraint.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For instance, Owen et al . () found that the probability for US firms to sell assets is nearly 10 percent higher for a one standard deviation decrease in the number of antitakeover restrictions (higher shareholder rights). Event studies also show that the market reaction to acquisitions is more positive for well‐governed acquirers, which suggests that they are more careful in their acquisition decisions and less prone to overpaying for the target (Masulis et al ., ).…”
Section: Propositionsmentioning
confidence: 99%